Kazakhstan-China energy projects - Nursultanova, Л.Н.; Atayeva, Т.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
Energy factor began to play in world politics no less important than the military factor, it led to the formation and further development of energy diplomacy as a tool of international politics. In connection with this, the energetic attitude of the People’s Republic of China, which eastern neighbor of Kazakhstan, is very important.This article analyzes main stages of oil and gas projects implementation between two states, which have practical significance for both republics.Both Republics on ongoing basis are reviewing the results of the implementation of decisions taken at the 9th meeting of the Subcommittee.In addition, the current state and prospects of cooperation in the oil and gas and nuclear industries, as well as cooperation in the field of electricity, renewable energy and the implementation of joint projects are discussed.Among the leaders in attracting investments is the fuel and energy sector, where for 26 years of development of the country, about 200 billion dollars of direct foreign investments were attracted. Today the industry does not give up these positions: currently, three large projects - Tengiz, Kashagan and Karachaganak - are implementing expansion and production extension projects, with a total investment of $ 42.3 billion.